2003
DOI: 10.1073/pnas.2336126100
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to psychotherapy versus pharmacotherapy in patients with chronic forms of major depression and childhood trauma

Abstract: Major depressive disorder is associated with considerable morbidity, disability, and risk for suicide. Treatments for depression most commonly include antidepressants, psychotherapy, or the combination. Little is known about predictors of treatment response for depression. In this study, 681 patients with chronic forms of major depression were treated with an antidepressant (nefazodone), Cognitive Behavioral Analysis System of Psychotherapy (CBASP), or the combination. Overall, the effects of the antidepressan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
259
6
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 714 publications
(294 citation statements)
references
References 21 publications
(13 reference statements)
18
259
6
5
Order By: Relevance
“…Although, for example, improvements in socioeconomic condition and in IQ remain a largely unmet target, effective preventive strategies exist for maltreatment (28). Therapeutic interventions including psychological and pharmacological treatment also might reverse the long-lasting effects of maltreatment (29,30). Third, childhood maltreatment is a pleiotropic risk factor influencing multiple pathophysiological pathways and outcomes [e.g., psychiatric disorders (31), health behaviors (19), and crime (12)].…”
Section: Resultsmentioning
confidence: 99%
“…Although, for example, improvements in socioeconomic condition and in IQ remain a largely unmet target, effective preventive strategies exist for maltreatment (28). Therapeutic interventions including psychological and pharmacological treatment also might reverse the long-lasting effects of maltreatment (29,30). Third, childhood maltreatment is a pleiotropic risk factor influencing multiple pathophysiological pathways and outcomes [e.g., psychiatric disorders (31), health behaviors (19), and crime (12)].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research suggests that the dexamethasone/CRF test may reveal elevated cortisol and ACTH levels only in those depressed individuals who have also suffered severe stress in childhood [19]. Nemeroff et al [20] reported that such patients respond to cognitive-behavioral therapy better than to an antidepressant. …”
Section: Subtypes Of Depressionmentioning
confidence: 99%
“…It integrates cognitive-emotional, behavioral, interpersonal, and psychodynamic/psychoanalytical theories and strategies across schools by directly addressing the specific psychopathology. In most of the outpatient studies CBASP proved to be an effective treatment, especially in combination with medication [3], in patients with childhood trauma [4], early onset [5], and with a long duration of treatment [6]. One study found no difference between CBASP, supportive therapy, or optimized pharmacotherapy as an augmentation strategy of medication partial response or nonresponse [7].…”
Section: Introductionmentioning
confidence: 99%